570 mV photovoltage, stabilized n-Si/CoOx heterojunction photoanodes fabricated using atomic layer deposition. Issue 3 (26th January 2016) - Zhou, Xinghao; Liu, Rui; Sun, Ke; Papadantonakis, Kimberly M.; Brunschwig, Bruce S.; Lewis, Nathan S.
Abstract : Deposition of a 50 nm thick CoO x layer on planar n-Si yields stable, high-performance photoanodes for water oxidation. Abstract : Heterojunction photoanodes, consisting of n-type crystalline Si(100) substrates coated with a thin ∼50 nm film of cobalt oxide fabricated using atomic-layer deposition (ALD), exhibited photocurrent-onset potentials of −205 ± 20 mV relative to the formal potential for the oxygen-evolution reaction (OER), ideal regenerative solar-to-O2 (g) conversion efficiencies of 1.42 ± 0.20%, and operated continuously for over 100 days (∼2500 h) in 1.0 M KOH(aq) under simulated solar illumination. The ALD CoO x thin film: (i) formed a heterojunction with the n-Si(100) that provided a photovoltage of 575 mV under 1 Sun of simulated solar illumination; (ii) stabilized Si photoanodes that are otherwise unstable when operated in aqueous alkaline electrolytes; and, (iii) catalyzed the oxidation of water, thereby reducing the kinetic overpotential required for the reaction and increasing the overall efficiency relative to electrodes that do not have an inherently electrocatalytic coating. The process provides a simple, effective method for enabling the use of planar n-Si(100) substrates as efficient and durable photoanodes in fully integrated, photovoltaic-biased solar fuels generators.